Gaussian Tetranacci Numbers - Taşcı, Dursun; Acar, Halime (Communications in Mathematics and Applications, 2017)
In this paper, we define Gaussian Tetranacci sequence. Moreover, we give generating function, Binet-like formula, sum formulas and matrix representation of Gaussian tetranacci numbers.